2016
DOI: 10.3139/113.110465
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Efficacy of Laundry Detergents with Regard to Time and Temperature in Domestic Washing Machines

Abstract: In times of low-temperature washing, laundry hygiene gains importance, as microbial contaminations on textiles can cause infection transmission and malodour formation. This study systematically investigated the antimicrobial effect of laundry detergents (solid and liquid market detergents) with regard to time and temperature in domestic washing machines. To evaluate the microbial reduction, cotton swatches contaminated with Staph. aureus, Ent. hirae, Ps. aeruginosa, C. albicans and T. mentagrophytes were washe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…; Honisch et al . , ). Interestingly, although the TAED‐mediated activation of percarbonate or perborate is temperature‐dependent and should work best at temperatures of above 40°C, an additional antimicrobial effect can already be observed at lower temperatures (Honisch et al .…”
Section: Factors Influencing the Hygiene Efficacy Of Launderingmentioning
confidence: 99%
See 2 more Smart Citations
“…; Honisch et al . , ). Interestingly, although the TAED‐mediated activation of percarbonate or perborate is temperature‐dependent and should work best at temperatures of above 40°C, an additional antimicrobial effect can already be observed at lower temperatures (Honisch et al .…”
Section: Factors Influencing the Hygiene Efficacy Of Launderingmentioning
confidence: 99%
“…There are only few investigations that allow observation of this detergency effect of surfactants on micro-organisms. Honisch et al (2016) recently investigated laundry processes with and without detergents and found little or no effects when comparing the remaining microbial load on artificially contaminated swatches after laundering in a domestic washing machine. Only S. aureus (and to a lesser extent Enterococcus hirae) exhibited a considerably higher LR when washed with detergent compared to water alone, probably due to a better removal of bacterial cells from the fabric, since suspension tests virtually show no antimicrobial effects when detergents are added (Brands et al 2016).…”
Section: Factors Influencing the Hygiene Efficacy Of Launderingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several suitable processes to investigate the antimicrobial efficacy of domestic laundering processes. The determination of the logarithmic reduction (LR) using artificially contaminated cotton swatches (biomonitors) is very common (Block et al, ; Honisch et al, , ). These biomonitors are laundered in a washing machine considering parameters such as the duration of the main wash cycle, the nominal main wash temperature, and the type of detergent.…”
Section: Methodsmentioning
confidence: 99%
“…The surfactants in laundry detergents are known to function as antimicrobial agents against various microbes Munk et al, 2001;Honisch et al, 2016 , but the microorganisms resistant to the killing action of the surfactants have been isolated Maeda et al, 1996;Munk et al, 2001 . Therefore, attachment of the surfactant-resistant bacteria, especially human pathogenic ones, to clothes or beddings may increase the risk of infectious diseases.…”
mentioning
confidence: 99%